Subsurface Organic Amendment Plus Plastic Mulching Promotes Salt Leaching and Yield of Sunflower. (1st January 2019) - Zhang, Hongyuan; Pang, Huancheng; Lu, Chuang; Zhang, Xu; Li, Yuyi
Abstract : Core Ideas: Salt reduction effect of organic amendment with mulch intensified with years. Organic amendment gradually reduced soil pH within the 10‐ to 40‐cm layer. Organic amendment increased the soil organic matter and available nutrients. The sunflower yield was highest under the organic amendment with plastic mulching. In order to evaluate the effects of subsurface organic amendment plus plastic mulching on soil salinity, soil pH, available nutrients and crop growth on saline–alkali soils, four management practices were conducted in 2015–2016, including plowing without plastic mulching (CK), plowing plus plastic mulching (PM), subsurface (10–30 cm) treatment with organic manure (OM), and OM plus plastic mulching (PM + OM). The result showed that OM and PM + OM enhanced the salt leaching after irrigation and regulated salt distribution to facilitate crop growth. Compare with CK, OM, and PM + OM reduced pH of 10to 30 cm by 0.36 to 0.6 in 2015 and 0.30 to 0.45 in 2016 ( P < 0.05), respectively. Relative to that of CK, soil organic matter, available N, P, and K of 0 to 40 cm under OM and PM + OM increased by 53.77 to 73.11%, 63.65 to 69.51%, 406.06 to 381.31%, 266.42 to 229.80% in 2015, and by 45.06 to 68.38%, 52.25 to 49.34%, 603.23 to 612.75%, 166.32 to 132.88% in 2016 ( P < 0.05). Compared with CK and PM, PM + OM increased sunflower yield by 45.08 and 19.37% in 2015, by 24.29 and 6.62% in 2016 ( P < 0.05), mainly due to a reduction of pH, the increase of soil organic matter and available nutrient, high water after irrigation as well as regulation of the water and salt. Therefore, amending the subsurface layer with organic manure combined with plastic mulching is a viable option for improving sunflower production in the saline–alkali soil of Hetao Irrigation District of Inner Mongolia or other areas with similar soil conditions.